Investigations into Magic, an Edition and Translation of Martín Del Río's Disquisitionum magicarum libri sex : Volume 4 - Maxwell-Stuart, Peter, (Heterodoxia Iberica ;, 2023)
The sixteenth century saw the world as being mortally threatened by Satan who was encouraged by the widespread popularity of magic and other occult practices. Church and society struck back to defend people from this tidal wave of wickedness. Del Río's panoramic and detailed treatise provided a powerful weapon in that battle. Far from dry scholarship, however, 'Investigations' is an engaging, fascinating, earnest conversation between Del Río and his readers and a major contribution to understanding key aspects of everyday sixteenth century behaviour and the problem of evil.